Reduced and unstratified crust in CV chondrite parent body - Clément Ganino (Nature Portfolio, 2017)
Meteorites may unlock the history of the early solar system. Here, the authors find, through Ca-Fe-rich secondary phases, that the distinction between reduced and oxidized CV chondrites is invalid; therefore, CV3 chondrites are asteroid fragments that percolated heterogeneously via porous flow of hydrothermal fluid.